Pendampingan Pengembangan Micro Reading Skills Berbasis Teks bagi Guru dan Siswa SMPN 13 Dumai - Yulianto Yulianto; Sri Yuliani; Farhana Farhana; Kanza Firza Putri (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aimed to increase the knowledge and competence of teachers and students regarding micro reading skills as a basic reading skill and to solve problems related to reading English text activities. This activity was conducted using the mentoring method through presentation, practice, and demonstrations. At the same time, data analysis was carried out qualitatively by directly observing changes in the ability of teachers and students to develop micro-reading skills provided during the mentoring and teaching process. The results obtained from this community service activity were an increase in teacher knowledge and students' abilities in micro reading skills to solve problems reading English texts, especially vocabulary topics, sentence comprehension, cohesive devices, themes, and patterns of thematic development. Teachers' and students' enthusiasm to participate in text-based micro-reading skills assistance made reading comprehension better and more communicative.